Influence Competence And Placement of Employee On Employee Performance At PT. Xylo Indah Pratama in Musi Rawas Regency of Muara Beliti - Ronal Aprianto; Fitria; Suyadi; Suwarno; Yulpa Rabeta (Journal of Social Science, 2020)
This research was conducted to determine the effect of employee competency and placement on employee performance at PT. Xylo Indah Pratama Muara Beliti Musi Rawas Regency. The results of this study indicate that there is a significant effect between Competency and Employee Placement on Employee Performance Keywords : Competence, Employee placement, Employee performance